2018
DOI: 10.20473/bhsj.v1i1.8226
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of High-sensitivity C-reactive Protein Level between Chronic Kidney Disease Stages

Abstract: Aim : This research is to evaluate the hs-CRP level comparison between CKD stages in Dr. Soetomo General Hospital Surabaya.Methods: An analytic observational cross-sectional study, evaluating the differences of hs-CRP level between CKD stages in 72 patients (mean age 55.49±7.62 years, the ratio between male:female was 1:1.48, mean BMI 24.18±3.64 kg/m2, 36.11% diabetics, 43.05% on ACEI/ARB, 29.16% on statin), recruited from Nephrology Outpatient Clinic, Dr Soetomo General Hospital, Surabaya, from January to May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This was explained with the small sample of 72 subjects. 31 The latest research by a group of Chinese authors showed that long-term exposure to high CRP values was associated with an increased risk of developing CKD. 32 NLR is a cheap, routinely used, and repeatable test, and many studies have found that it can be an indicator of systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This was explained with the small sample of 72 subjects. 31 The latest research by a group of Chinese authors showed that long-term exposure to high CRP values was associated with an increased risk of developing CKD. 32 NLR is a cheap, routinely used, and repeatable test, and many studies have found that it can be an indicator of systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive renal impairment is associated with worsening systemic inflammation and elevated levels of C-Reactive Protein (CRP) detected along with other acute-phase proteins. Monitoring CRP levels in CKD patients, especially in the late stage, has been implemented because CRP is an inflammatory marker which has a stable condition and does not 5,6 show significant circadian variability.…”
Section: Metana Puspitasari MI Diah Pramudianti Yuwono Hadisupartomentioning
confidence: 99%
“…Hematological investigations, especially full blood counts, are good indicators in health and disease states, helping to understand the real disease presentation juxtaposed to the features in the patients (George et al, 2015). This study showed decrease in Hb, PCV and RBC in HD patients compared with diabetic patients and control; this decrease is due to hematuria and gastrointestinal blood loss or due to a decrease in the production of erythropoietin by the kidney, leading to decreased production of RBC in the bone marrow, and anemia that causes hypoxia; Hypoxia will increase hepsidin that causes functional iron deficiency through inhibition of iron absorption in the intestine and inhibition of Fe distribution in blood circulation as more is stored in macrophages or spleen (Abd Rabo et al,2016, Thaha et al, 2018.…”
Section: Human High Sensitivity C-reactive Protein (Hs-crp) Level In Four Study Groupsmentioning
confidence: 99%